PENERAPAN MODEL PEMBELAJARAN BERBASIS MASALAH UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS VII4 SMP NEGERI 14 PEKANBARU - Wulandari, Wimvy Tri; Sakur, Sakur; Jalinus, Jalinus (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research is a classroom action research that aims to improve the learning process and improve mathematics learning outcomes by applying the Problem Based Learning model. This research consists of two cycles, each of which consists of four stages, namely planning, implementation, observation, and reflection. At the end of each cycle Quizzes are carried out. The data needed are data on teacher and student activities collected by observation techniques and analyzed by descriptive narrative and mathematics learning outcomes data collected by tests and analyzed by descriptive statistics. Students are seen as actively participating and increasingly independent in the learning process carried out, such as in solving mathematical problems given, presenting the results of problem solving and providing learning conclusions. The results showed that the implementation of the learning process in the second cycle had improved from the implementation of the cycle I. Weaknesses in the first cycle were improved in the implementation of the second cycle according to the improvement plan after reflection cycle I. The number of students who achieved the Minimum Completion Criteria (KKM) increased from basic scores until Quiz I and II. The results of this study indicate that the application of the Problem Based Learning model can improve the learning process and improve mathematics learning outcomes of students in class VII_4 SMP Negeri 14 Pekanbaru in the odd semester of the school year 2018/2019.Key Words: Mathematics Achievement, Problem Based Learning, Class Action Research